2002
DOI: 10.1136/bjo.86.7.782
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of congenital and paediatric cataract in an Australian population

Abstract: Background/aim: Paediatric cataract is a major cause of childhood blindness. Several genes associated with congenital and paediatric cataracts have been identified. The aim was to determine the incidence of cataract in a population, the proportion of hereditary cataracts, the mode of inheritance, and the clinical presentation. Methods: The Royal Children's Hospital and the Royal Victorian Eye and Ear Hospital have a referral base for almost all paediatric patients with cataracts in south eastern Australia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
4
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 51 publications
11
99
4
6
Order By: Relevance
“…Incidence studies included in this review were conducted in Sweden, 35 Denmark, 36 the UK, 37 and Australia. 38 These are all high-income economies; we found no incidence studies based in low-to middleincome economies.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Incidence studies included in this review were conducted in Sweden, 35 Denmark, 36 the UK, 37 and Australia. 38 These are all high-income economies; we found no incidence studies based in low-to middleincome economies.…”
Section: Discussionmentioning
confidence: 68%
“…Incidence was reported in four studies [35][36][37][38] and ranged from 1.8 to 3.6 per 10 000 per annum. Laterality was reported in two of these studies 35,37 and gender breakdown was reported in three studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no mention of unilaterality or bilaterality in the series. Wirth,9 in his series of 29 congenital cataract cases, found Down's syndrome in 62% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…These include TORCH screen, karyotyping, urinalysis for reducing agents and organic amino acids, measurement of plasma galactokinase levels and basic blood tests (such as full-blood count and liver function tests). 3 Despite the publication of several care pathways guiding management and investigation of CC, 2,3 the proportion of cases of bilateral CC in which the underlying cause was identified has been shown in the past to be low. Multiple professionals are often involved, with many appointments and investigations needed as part of the traditional care pathway of the child with cataract.…”
Section: Introductionmentioning
confidence: 99%